Magnetic Shielding With High-Tc (YBa2Cu3O7-δ)1-xAgx Superconducting Tubes - H. Castro; E. Holguín; J. F. Loude; L. Rinderer (Active and Passive Electronic Components)
We present typical results of experiments carried out in (YBaCuO)1-xAgx tubular samples, for different values of the silver concentration x, having in mind the possible use of this material as a magnetic shield. We measured the times governing the dynamics of magnetic flux penetration, on a microsecond time-scale, and tried to correlate them with d.c. measurements of the resistivity and the critical transport current density, using a simple theoretical model based on the flux-flow régime.